Changes in intestinal absorption of nutrients and brush border glycoproteins after total parenteral nutrition in rats. - Miura, S (1992)
The effect of total parenteral nutrition on nutrients absorption and glycoprotein changes of brush border membrane was examined in rat small intestine. In total parenteral nutrition rats, a marked decrease in activity of brush border enzymes was observed mainly in the proximal and middle segments of the intestine. Galactose perfusion of jejunal segment showed that hexose absorption was significantly inhibited, while intestinal absorption of glycine or dipeptide, glycylglycine was not significantly affected by total parenteral nutrition treatment. When brush border membrane glycoprotein profile was examined by [3H]-glucosamine or [3H]-fucose incorporation into jejunal loops, significant changes were observed in the glycoprotein pattern of brush border membrane especially in the high molecular weight range over 120 kDa after total parenteral nutrition treatment, suggesting strong dependency of glycoprotein synthesis on luminal substances. Molecular weight of sucrase isomaltase in brush border membrane detected by specific antibody showed no significant difference, however, in total parenteral nutrition and control rats. Also, molecular weight of specific sodium glucose cotransporter of intestinal brush border membrane detected by selective photoaffinity labelling was not altered in total parenteral nutrition rats. It may be that prolonged absence of oral food intake may produce significant biochemical changes in brush border membrane glycoprotein and absorptive capacity of small intestine, but these changes were not observed in all brush border membrane glycoproteins.